Global monitoring report. - World Bank.; International Monetary Fund. (Washington, D.C. International Bank for Reconstruction and Development/The World Bank, 2004)
"Policies and actions for achieving the Millenium Development Goals and related outcomes"
Keywords: Economic development -- Periodicals; Economic policy -- Periodicals